Factors influencing relapse of schizophrenia in Hospital Universiti Sains Malaysia (HUSM), Kelantan - Ling Shin, Ru (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Schizophrenic patients relapse so frequently that they must spend 15 to 20% of their time in a psychiatric institution and occupy a full third of all psychiatric beds (Maurer & Biehl 1988 as cited in Ayuso-Gutierrez & del Rio Vega, 1997). Relapse of schizophrenia has many consequences such as increased hospitalization, increased cost of illness, and increased burden on family members and health care providers as well. However, prevention of relapse is important to prevent poor long-term outcome. Therefore, it is crucial to find out the underlying factors which can influence relapse of schizophrenia. Thus, this study aims to determine the influencing factors such as sociodemographic data, health status and patient attitude; and family support and their association with relapse schizophrenia. The conceptual framework that guided this study was developed and modified from Ariff (2000). This was a cross-sectional, descriptive study. The target population was inpatient at Psychiatric Ward in Hospital Universiti Sains Malaysia, (HUSM), Kelantan. The study recruited 13 psychiatric inpatients (mean age: 37.8) and caregivers who met the inclusion criteria. After informed consent was taken from caregivers, the researcher interviewed the caregiver using demographic questionnaire and assessed the presence of symptoms of schizophrenic patient using Positive and Negative Syndrome Scale (PANSS). The data were analyzed using descriptive statistics and inferential statistics: Independent t-test and ANOVA. Findings of this study indicated that there were association between sex (t=-2.20, p=0.05), living status (t=2. 71, p=0.02), and frequency of oral medication per day on relapse of schizophrenia (t=2.14, p=0.05). This study highlighted some important influencing factors such as sex, living status, and frequency of oral medication per day that have association on relapse of schizophrenia. It is hoped that with the findings nurses can provide more effective care prevention to reduce relapse for schizophrenia patients. However, it is suggested that future research should focus on larger samples and on different ethnic groups.